City-regional imaginaries and politics of rescaling. Issue 1 (2nd January 2021) - Davoudi, Simin; Brooks, Elizabeth
ABSTRACT: This paper proposes a new conceptualization of scale as performative imaginary and deploys that to explore the what, the why and the how questions of scalar fixing. Drawing on city-regionalization in England, it argues that a distinct imaginary of city-regions as economic- and city-centric spaces has been normalized through two forms of knowledge: one rationalizing the scalar positioning of this imaginary, the other demarcating its spatial boundaries. It shows that despite the alignment between enacted scale (what), scalar imaginary (how) and neoliberal political project (why), institutionalization of this imaginary has failed, leading to variable geometries of subnational governance.